Evaluation of Tracheal Aspirate Cultures of Patients Followed with Home Mechanical Ventilators - Esra AKYÜZ ÖZKAN; Demet GÜR VURAL (Ahi Evran Medical Journal, 2023)
Purpose: To investigate the underlying diseases, and complaints of patients upon admission, isolated microorganisms from tracheal aspirate (TA) samples and their resistance to antibiotics in patients followed up with a home mechanic ventilator (HMV).